Posted by Gabby on Thursday, July 29, 2010 at 11:41pm.
√27a^3 = 3a√3a
√(3a) + 9√(27a^3)
= √(3a) + 27a√(3a)
= √(3a)( 1 + 27a)
not much gained here, poor question if the instructions were to "simplify"
algebra - (sqr root of 2 + 3*sqr root of 5)(sqr root of 2-3*sqr root of 5)
Algebra 2 - Ok, so I'm trying to find the inverse of each function. We'...
Calc - How close is the semi circle y= sqr.root of 16-x^2 to the point (1, sqr....
Algebra2/Trig - sqr(x^2-4)+(x^2)/x^2+1 I got ((x^2+1)*sqr(x^2-4)+x^2)/x^2+1 But ...
Math - Find the quotient function f/g for f(x)=sqr(x+1) and g(x)= sqr( x-1). My...
Math - Find the quotient function f/g for f(x)=sqr(x+1) and g(x)= sqr( x-1). My ...
algebra 1 - sqr 10 times sqr 16 over sqr 5
Algebra - For what values does the sqr root of 2x = x square root 2 ?
Algebra 2 - f(x) = sqr.root of x/6
algebra 1 - 1 over 2 sqr 32 times sqr 2 simplify the expression
For Further Reading